1998
DOI: 10.1007/s004210050398
|View full text |Cite
|
Sign up to set email alerts
|

Hindlimb suspension reduces muscle regeneration

Abstract: Exposure of juvenile skeletal muscle to a weightless environment reduces growth and satellite cell mitotic activity. However, the effect of a weightless environment on the satellite cell population during muscle repair remains unknown. Muscle injury was induced in rat soleus muscles using the myotoxic snake venom, notexin. Rats were placed into hindlimb-suspended or weightbearing groups for 10 days following injury. Cellular proliferation during regeneration was evaluated using 5-bromo-2'-deoxyuridine (BrdU) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 17 publications
2
32
0
3
Order By: Relevance
“…identical changes occur in the muscles during unloading produced by caudal suspension in animals or prolonged bed rest in humans (Ferrando et al 1996, Bamman et al 1998, Mozdziak et al 1998, Wehling et al 2000. Muscle organ cultures sent in spaceflight also demonstrate atrophy in response to microgravity (Vandenburgh et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…identical changes occur in the muscles during unloading produced by caudal suspension in animals or prolonged bed rest in humans (Ferrando et al 1996, Bamman et al 1998, Mozdziak et al 1998, Wehling et al 2000. Muscle organ cultures sent in spaceflight also demonstrate atrophy in response to microgravity (Vandenburgh et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In experiments using the rat hindlimb suspension model to mimic disuse atrophy experienced in space, the mass of soleus muscle exposed to anti-gravity conditions rapidly decreased to one half of initial values after one week. Shultz (Mozdziak et al 1998) and Edgerton's groups (Allen et al 1997) showed a decrease in muscle size and in the number of muscle cells, which likely reflects disuse-induced apoptosis of muscle cells. Although muscle cells are known to undergo size changes, the mechanisms by which disuse induces decreases in muscle size and apoptosis are unclear.…”
Section: Response Of Stress Protein 'B-crystallin In Muscles To Mechamentioning
confidence: 94%
“…This phenomenon was closely associated with the inhibited increases of satellite cell and myonuclear number. It was also reported that gravitational unloading downregulates the satellite cell mitotic activity (11,(35)(36)(37)49). Furthermore, atrophy and regrowth of muscle fibers in soleus (59) and adductor longus (41) of Wistar Hannover rats were closely related to the number of satellite cells, which is also positively correlated with the distribution of myonuclei.…”
mentioning
confidence: 88%